A New High-Spin Level Scheme of ^128I - 王海霞 张玉虎 丁兵 周小红 张宁涛 柳敏良 马英君 Y. Sasakiz K. Yamada H. Ohshima S. Yokose M. Ishizuka T. Komatsubara K. Furuno (Chinese physics letters, 2010)
High-spin states in the beam energies. A new and 72 γ transitions odd-odd nucleus ^128I are investigated via the ^124 Sn（^7 Li,3n）^128 I reaction at 28 and 32 Me V level scheme of 12sI is established up to high-spin states at I^π = 16, including 48 levels The present level scheme is largely different from the one in a recent publication due to identification of several doublet and triplet γ transitions and their proper placements in the level scheme. The high-spin level structure exhibits no obvious collective properties and is possibly associated with two and multi-quasiparticle configurations.